(untitled) (Journal of Imam Al-Kadhim College, 2024)
The guardianship of banks is an exceptional, temporary legal situation according to which the Central Bank appoints a trustee of a bank to restructure it in legally defined cases with the aim of achieving financial and administrative stability, and that the parties to the guardianship of banks consist of the Central Bank (the trustee) as an independent, non-profit public institution specialized in politics Cash and the issuance of the national currency and the second party is the defaulting bank placed under guardianship (the recommended one), which are non-specialized credit institutions that mainly receive public deposits that can be withdrawn on demand or after a short period, or deal mainly in short-term credit, The third party guardian is a natural and legal person, whether alone or with a committee of persons appointed by the Central Bank in accordance with the law. He is considered one of the employees of the Central Bank who manages the troubled bank under his supervision for a specified period and has all powers for the purpose of restoring the bank to its normal status.